Evaluasi Pengalaman Pengguna dari Perspektif Mahasiswa pada Eling dan Google Classroom (Kasus: Mahasiswa SAP Sistem Informasi Angkatan 2019 Fakultas Ilmu Komputer Universitas Brawijaya) - Ananda Apriliah Sari; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Eling is an LMS that contains information on the implementation of learning activities at Filkom. Google Classroom is a Learning Management System (LMS) service product that aims to simplify and organize the learning process, assess assignments and improve communication without having to meet face-to-face. Currently, Filkom UB uses two LMS, namely Google Classroom and Eling for online learning. So far, it is not known what the student's perspective is when using the LMS Google Classroom and Eling. Therefore, the researcher wants to evaluate the user experience from the student's perspective on these two LMS. If the student's perspective is known, it is hoped that the problems encountered by student users with each LMS and the needs of users will be known, which will later provide benefits for improvements to LMS services. The researcher also intends to find out and compare how good the user experience is felt by LMS users. This LMS user experience test uses usability testing. Usability testing is used to identify problems and determine user responses to show how effective and efficient the LMS is to help users achieve their goals. The results of the interviews obtained problems, needs and preferences of respondents in each LMS. The results of testing the effectiveness, efficiency and satisfaction can be seen that Google Classroom gets a higher rating on all scenario testing and the results of the SUS questionnaire.